Neonatal handling: An overview of the positive and negative effects. Issue 8 (4th August 2014) - Raineki, Charlis; Lucion, Aldo B.; Weinberg, Joanne; Sullivan, Regina M.
ABSTRACT As one of the first rodent models designed to investigate the effects of early‐life experiences, the neonatal handling paradigm has helped us better understand how subtle changes in the infant environment can powerfully drive neurodevelopment of the immature brain in typical or atypical trajectories. Here, we review data from more than 50 years demonstrating the compelling effects of neonatal handling on behavior, physiology, and neural function across the lifespan. Moreover, we present data that challenge the classical view of neonatal handling as an animal model that results only in positive/beneficial outcomes. Indeed, the overall goal of this review is to offer the suggestion that the effects of early‐life experiences—including neonatal handling—are nuanced rather than unidirectional. Both beneficial and negative outcomes may occur, depending on the parameters of testing, sex of the subject, and neurobehavioral system analyzed. © 2014 Wiley Periodicals, Inc. Dev Psychobiol 56: 1613–1625, 2014.